PIATTAFORME UAV AD ALA FISSA E ROTANTE PER IL MONITORAGGIO AMBIENTALE - Tucci, Grazia; Bonora, Valentina; Guardini, Nadia (GEOmedia, 2014)
The UAV systems have achieved a considerable attention in recent years as platforms for data acquisition and measuring; the extraction of terrain models, orthophotos and 3D textured models can be applied for several purposes, including surveying and monitoring of the landscape for the assessment and management of risks to which it is subjected. In this paper we present some of the possibilities offered by UAV systems through application to two case studie in order to evaluate the strengths and weaknesses.